The features of reactions to acute stress of neuro-endocrine-immune complex, metabolome, ECG and gastric mucosa in rats with various state of innate muscular endurance and resistance to hypoxia - Oksana Melnyk; Ivanna Chendey; Walery Zukow; Oleksandr Plyska; Igor Popovych (Kazimierz Wielki University, 2023)
Background. It is known about wide variety of individual reactions to stress explained by genetics factors. On the other hand, it is also known about aerobic fitness variability between individuals. From the above it follows the hypothesis that inter-individual differences in normal conditions determine the characteristics of the body's response to acute stress. The purpose of this study is to test the hypothesis. Material and methods. The experiment is at 58 rats (28 males) Wistar line. Animals were tested for resistance to hypoxic hypoxia and aerobic muscular performance by swimming test. On the basis of the received data two qualitatively equivalent groups in a ratio 10/48 were formed. After a week of recovery over the next 10 days, one animal remained intact and 5 other rats were exposed to water-immersion and restraint stress. The next day after stress, the ECG recorded and some endocrine, metabolic and immune parameters determined as well as erosive-ulcerative lesions of the gastric mucosa evaluated. Results. Four clusters by hypoxic and swimming tests were created retrospectively: normal resistance to hypoxia and muscular endurance (n=11); moderately reduced resistance to hypoxia and normal swimming test (n=25); drastic increased swimming test and normal hypoxic test (n=3); significantly increased resistance to hypoxia and normal swimming test (n=9). Each cluster is characterized by specific (correctness of classification 100%) post-stress changes in 6 neuro-endocrine, 12 immune, 10 metabolic and 2 ECGs parameters, as well as the index of damage to the gastric mucosa. The swimming test determines the post-stress state of the registered parameters by 63,8%, the hypoxic test - by 57,5%, and taken together - by 79,1%. Conclusion. The post-stress neuro-endocrine, immune and metabolic parameters as well as injuries of myocardium and gastric mucosa in rats are determined significantly by innate muscular endurance and resistance to hypoxia.